2017
DOI: 10.17129/botsci.667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light quality on growth, total gypenosides accumulation and photosynthesis in Gynostemma pentaphyllum

Abstract: Background: Gynostemma pentaphyllum is a kind of shade-tolerant plants. It can synthesize and accumulate gypenosides in large amounts. The gypenosides are a valuable medicine that against hypertension, hyperlipemia, obesity, neurological disorder, inflammation, immune-modulation, diabetes and tumours. Hypotheses: Light quality was proved to affect the growth and gypenosides accumulation obviously in G. pentaphyllum, and it affects the photosynthesis certainly. So, some relationships may exist among these param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These results are in agreement with those of Giorgioni (2010) determined the effect of light intensities (approximately 4, 7, 11 and 20 µmol m -2 s -1 ) on growth, foliar micromorphology, essential oil content, yield and chemical composition of Ocimum gratissimum L., their study confirmed that biomass production of different organs, root: shoot ratio and leaf mass per area were linearly increased with increased light availability [5]. Assessed that plants grown at the highest light intensities produced the greatest numbers of flower stalks, and these were heavier than those produced in the shade [6]. found that light intensity had remarkable effects on plant growth, total gypenosides accumulation and photosynthesis, white light had increased in biomass, stem diameter and newly sprouted leaves than homogeneous light did, compared with blue and green light, white light presented a higher content of total gypenosides which was closest to that of red light, suggesting the effect of white light on gypenosides accumulation was involved in red light.…”
Section: Discussionmentioning
confidence: 60%
“…These results are in agreement with those of Giorgioni (2010) determined the effect of light intensities (approximately 4, 7, 11 and 20 µmol m -2 s -1 ) on growth, foliar micromorphology, essential oil content, yield and chemical composition of Ocimum gratissimum L., their study confirmed that biomass production of different organs, root: shoot ratio and leaf mass per area were linearly increased with increased light availability [5]. Assessed that plants grown at the highest light intensities produced the greatest numbers of flower stalks, and these were heavier than those produced in the shade [6]. found that light intensity had remarkable effects on plant growth, total gypenosides accumulation and photosynthesis, white light had increased in biomass, stem diameter and newly sprouted leaves than homogeneous light did, compared with blue and green light, white light presented a higher content of total gypenosides which was closest to that of red light, suggesting the effect of white light on gypenosides accumulation was involved in red light.…”
Section: Discussionmentioning
confidence: 60%
“…Chlorophylls absorb primarily the red and blue wavelengths of light; therefore, these spectral compositions are particularly important in the photosynthetic activity of leaves. Comparing the effects of red and blue light, the photosynthetic activity (Pn) of leaves was induced more efficiently by red than by blue light in many studies (Lanoue et al, 2017; Peng et al, 2017; Yang et al, 2018); however, in other studies, the blue light was dominated (Li et al, 2020; Liang et al, 2021). The different light responses can derive from the growth conditions and depend on the species used.…”
Section: Introductionmentioning
confidence: 99%
“…13 Environmental factors have a significant influence on chemical constituents of mint species. The light-related factors, such as light intensity, 14,15 light quality, 16,17 and light period, 18,19 are the main factors that directly affect plant production and its composition. Hence, adjusting artificial light source plays an important role in optimizing production of desirable plants.…”
Section: Introductionmentioning
confidence: 99%